The Effect of Quantitative Easing on the Asset Correlation Structure of the Market - Růžička, Marek (2024)
This study investigates the influence of quantitative easing on the correlation structure of three assets in the US markets within the framework of Modern portfolio Theory. The research aims to determine if QE policies employed in the US market have influenced the interrelationships among these assets. Beginning with an overview of Modern Portfolio Theory, emphasizing the importance of diversification, the study examines the asset correlation calculations and provides a concise insight into the relationships between macroeconomic variables and asset returns. It then discusses the transmission mechanisms through which QE shapes the economy. The empirical analysis utilizes comprehensive dataset from American financial markets, employing statistical techniques to assess changes in asset correlations during QE periods. Contrary to initial hypothesis, findings indicate that QE did not have significant impact on the stock-corporate bond and stock-gold correlation. These findings suggest that other factors may play a more prominent role in determining asset correlations during QE periods. Future research should focus on identifying these factors and exploring their implications for market stability.